1993
DOI: 10.1002/ar.1092370205
|View full text |Cite
|
Sign up to set email alerts
|

Innervation distribution pattern, nerve ending structure, and fiber types in pigeon skeletal muscle

Abstract: Four fiber types have been characterized in different pigeon skeletal muscles according to their innervation pattern (nerve ending structure and innervation distribution) and histochemical properties (SDH and m-ATPase activities). All fast fibers, types IIA and IIB, present aggregated distribution of their nerve endings with "en plaque" structures and very low innervation frequencies. The two kinds of slow fibers recognized are multiple innervated and present higher innervation frequencies. However, type I fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…() used SDH localization and ATP histochemistry to analyse the fibre components of twelve skeletal muscles collected from pigeons and chickens. Many studies have shown that the composition of each muscle related to flying ability is different (Wada et al., ; Torrella et al., ). The type IIa muscle fibre is actively involved in transporting energy during exercise (Torrella et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() used SDH localization and ATP histochemistry to analyse the fibre components of twelve skeletal muscles collected from pigeons and chickens. Many studies have shown that the composition of each muscle related to flying ability is different (Wada et al., ; Torrella et al., ). The type IIa muscle fibre is actively involved in transporting energy during exercise (Torrella et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the composition of each muscle related to flying ability is different (Wada et al., ; Torrella et al., ). The type IIa muscle fibre is actively involved in transporting energy during exercise (Torrella et al., ). In this study, pigeons that had been given l ‐carnitine had a higher component percentage of type IIa muscle fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial ATPase was used to reveal muscle capillaries (Fouces et al. 1993; Torrella et al. 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were incubated for 5 min in a buffered fixative (Viscor et al 1992) and stained for the following histochemical assays to identify the fibre types and capillaries: succinate dehydrogenase, SDH according to Nachlas et al (1957) and myofibrillar adenosine triphosphatase, mATPase (Brooke & Kaiser, 1970). Endothelial ATPase was used to reveal muscle capillaries Torrella et al 1993).…”
Section: Sample Preparationmentioning
confidence: 99%
“…With respect to other physiological and morphological characteristics, ST fibers fail to respond to single nerve impulses, slowly shorten when stimulated repetitively (Morgan and Proske, 1984), and have multiple "en grappe" nerve terminals (Hess, 1967), whereas slow-twitch (and fast-twitch) muscle fibers generate an action potential and exhibit a rapid rise in tension after nerve stimulation (Morgan and Proske, 1984;Torrella et al, 1993). Histochemically, avian SO fibers react like mammalian SO fibers, but avian SO fibers, like slow tonic fibers, are multiply innervated (Baier and Gatesy, 2000).…”
mentioning
confidence: 99%